(untitled) (Praxis Educativa, 2026)
Gestalt theory emerged in the cultural and intellectual context of interwar Germany, as a reaction to the reductionism of structuralism in psychology. It proposed that perception is an active and global process, where wholes are perceived before parts. Although initially highly influential, its "laws" were later questioned for their supposed universality, lack of neuroscientific basis, and neglect of the cultural, historical, and subjective context of the observer. However, its practical usefulness in audiovisual arts is still valued today. Understood not as dogma, but as a set of general principles of perceptual organization, Gestalt can enrich visual narrative, guiding attention and generating balance or tension as required by the work. Therefore, its critical incorporation into audiovisual training is proposed, especially in areas such as art direction, set design, and costume design, taking advantage of its expressive potential based on the narrative.